Solve for x in terms of y It was so interesting, but after 30 minutes I gave up.
Follow Math Help Forum on Facebook and Google+
y = x + 1/x xy = x^2 + 1 x^2 - xy + 1 = 0, quadratic in x, x = [-(-y) +/- ((-y)^2 - 4(1)(1))^1/2]/2 x = [y (+/-) (y^2 - 4)^(1/2)]/2 positive root: x = y/2 +[sqrt (y^ - 4)]/2 negative root; x = y/2 -[sqrt (y^ - 4)]/2 plot below of y = x + 1/x
Last edited by pacman; September 24th 2009 at 05:27 AM.
The above answer missed "2", it should be positive root: x = y/2 +[sqrt (y^2 - 4)]/2 negative root; x = y/2 -[sqrt (y^ 2- 4)]/2
thanks woodsmith, you have an eye of the eagle
View Tag Cloud